Influência da orografia da América do Sul na propagação de massas de ar frio para baixas latitudes: um experimento numérico para o mês de julho de 2000 - Mintegui, Jéssica Melo (2023)
Atmospheric phenomena are influenced by orography, especially near mountain ranges. Thus, the main goal of this study is to verify the South America orography influence in the synopitic transient disturbances responsible for the cold surges in this continent. The analysis was based on July 2000 events, where three cold air incursions to low latitudes (friagem) were documented. For this purpose, four numerical simulations were carried out using the Weather Research and Forecasting (WRF) model: one with a reduction in the orography of the Andes mountain range; the second with a reduction in the Brazilian Plateau (both with up to 10% of its total dimension); third that considers the two modifications combined. In general, the results showed the orography of the Andes and the Brazilian Plateau influence the position and displacement of transient disturbances associated with cold incursion to low latitudes.